1996
DOI: 10.1016/s0550-3213(96)00476-2
|View full text |Cite
|
Sign up to set email alerts
|

ℵ0-extended supergravity and Chern-Simons theories

Abstract: We give generalizations of extended Poincaré supergravity with arbitrarily many supersymmetries in the absence of central charges in threedimensions by gauging its intrinsic global SO(N) symmetry. We call these ℵ 0 (Aleph-Null) supergravity theories. We further couple a nonAbelian supersymmetric Chern-Simons theory and an Abelian topological BF theory to ℵ 0 supergravity. Our result overcomes the previous difficulty for supersymmetrization of Chern-Simons theories beyond N = 4. This feature is peculiar to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Alternatively, the action (A.1) can be viewed as a BF-type theory coupled to matter chiral superfields. The importance of three-dimensional supersymmetric BF-type theories was pointed out in [34], where the authors studied the coupling of such models to supergravity as well as some aspects of their duality and mirror symmetry. More recently, in [19] it was shown that (A.1) corresponds to the classical action of the Abelian Gaiotto-Witten model [10] which is, in general, a Chern-Simons-matter theory with N = 4 supersymmetry.…”
Section: A1 Dualization Of the Abelian Gaiotto-witten Modelmentioning
confidence: 99%
“…Alternatively, the action (A.1) can be viewed as a BF-type theory coupled to matter chiral superfields. The importance of three-dimensional supersymmetric BF-type theories was pointed out in [34], where the authors studied the coupling of such models to supergravity as well as some aspects of their duality and mirror symmetry. More recently, in [19] it was shown that (A.1) corresponds to the classical action of the Abelian Gaiotto-Witten model [10] which is, in general, a Chern-Simons-matter theory with N = 4 supersymmetry.…”
Section: A1 Dualization Of the Abelian Gaiotto-witten Modelmentioning
confidence: 99%
“…The structure of the lagrangian (2.1) is very similar to that in section 2 in [6], but there are also differences. The most important one is that the gauge group G in the present case is completely arbitrary, and the gravitino is in the adjoint representation of G. There is no restriction on the gauge group G.…”
Section: ℵ 0 -Extended Local Supersymmetries With Arbitrary Gauge Groupmentioning
confidence: 71%
“…Some typical examples were given in [4] with the gauge groups OSp(p|2; IR) ⊗ OSp(q|2; IR), or with N = 8M and N = 8M − 2 supersymmetries in [5], or SO(N) symmetries in [6]. Another example is conformal supergravity CS theory with ∀ N -extended supersymmetries with local SO(N) gauge symmetries [8] [5].…”
Section: Introductionmentioning
confidence: 99%
“…Eighth, compared with a model presented in [15], the similarity is that the SO(N) gauge field A µ IJ is minimally coupled to the gravitino, while its field strength is vanishing by the BF -term. The difference is that the present system is more non-trivial, because of the σ -model physical fields on E 8(+8) /SO(16) in addition to other non-propagating fields.…”
Section: Topological So(16) -Gaugingmentioning
confidence: 99%
“…On the other hand, there has been an independent development related to supersymmetric Chern-Simons theories in 3D [14], in which it has been shown that certain ChernSimons theories in 3D can exist for arbitrary number of supersymmetries up to infinity [15].…”
Section: Introductionmentioning
confidence: 99%